Analisis Isi Konten Instagram @Prabowo dalam Membangun Citra pada Pemilihan Presiden 2024 - Ichsan Hidayat Rifaham; Ansar Suherman; Muh. Hidayatullah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to examine how the Instagram account @prabowo developed a strong character during the presidential era using character theory. A qualitative approach involving content analysis was used to evaluate the textual and visual elements in the analyzed Instagram posts. The findings of this study indicate that the main theme of the content is "strong leadership", which is conveyed through graphic and textual components. Textual elements, such as captions, highlight Prabowo's dedication to important issues such as national development and preventing corruption. The depiction of leadership integrity is achieved through the use of firm words and expressions. Analysis of visual elements shows that the use of beige and dark brown helps convey stability and trust. Prabowo is depicted as a patriotic leader who is close to the people, shown through backgrounds that display interactions with society and national symbols. Her confident and assertive demeanor, as well as her professional yet approachable demeanor, reduces feelings of peer pressure. Effective communication strategies involve emphasizing individuality, engagement with the community, incorporation of national symbols, and the use of striking imagery. This approach succeeds in building a strong and trustworthy image. This study highlights the important role of social media in political campaigns and the need for consistent textual and visual elements to convey key messages effectively. These findings are useful for social media practice, political campaign strategy, and political communication research.